Do South African fiscal reforms benefit women? - (:unkn) unknown (My University, 2021)
Economic reforms affect men and women differently. In South Africa, gender and racial disparities still exist in the labour market, with women being highly vulnerable. The South African economy is in a depressed situation, with high levels of debt and public deficit. To improve the financial situation of the country, the government has implemented two new fiscal reforms: increase Value-added tax (VAT) for all commodities by 1%, excluding food, and reduce public spending by 5%. This paper evaluates the impacts of both reforms on women from all population groups in terms of employment and poverty levels, by using a Computable General Equilibrium model with micro-simulations. The simulations reveal that both policies have negative impacts on agents, particularly households and firms and poverty levels among women of all population groups. The hike in VAT increases the number of poor households, with women more affected than men. The drop in public spending shows negative impacts for all agents, however, it has lower impacts on poverty levels than those occurring from increasing VAT. The results reveal that South African women, of all population groups, are more vulnerable to the negative impacts of both reforms than men.
Keywords: African Research